Peran Rumah Detensi Imigrasi dalam Pemenuhan Hak Asasi Manusia (HAM) Deteni : Studi Penelitian di Rumah Detensi Imigrasi Medan - Veronika Karolina Simamora; Yasmirah Mandasari Saragih; Lidya Rahmadhani Hasibuan (Asosiasi Penelitian dan Pengajar Ilmu Hukum Indonesia, 2024)
Medan Immigration Detention Center (Rudenim) is a technical implementing unit that carries out immigration functions as a temporary shelter for foreigners who are subject to administrative immigration actions in the Nangroh Aceh Darussalam and North Sumatra regions. There are several reasons why foreign nationals are placed in Rudenim, including being in the territory of the Republic of Indonesia without having a valid immigration permit, waiting for the repatriation or expulsion/deportation process, being subject to administrative immigration actions, having completed their sentence and not yet being able to be repatriated or deported. This study aims to determine the history, duties and functions of the Medan Immigration Detention Center and to determine the role of the Medan Immigration Detention Center in fulfilling the Human Rights (HAM) of detainees in the Medan Immigration Detention Center. The research method used is descriptive qualitative and uses a data collection method with a literature review through primary and secondary legal sources. Primary sources such as daily reports made by the Medan Immigration Detention Center, interviews with detainees and employees at the Medan Immigration Detention Center, and observations in the detention room building. As for the secondary sources in this journal, they include related laws and regulations. The results of the study indicate that Rudenim Medan has fulfilled human rights such as the right to worship, receive adequate health services and food, detainees are also given the opportunity to convey complaints, receive visits from family or sponsors, and communicate with representatives of their country. However, there are challenges in the implementation of human rights protection, including the lack of guards at Rudenim Medan and the lack of English language skills of Rudenim Medan officers and the presence of detainees who cannot speak English. Therefore, there needs to be continuous effort from officers at Rudenim Medan, the government and related institutions to strengthen the protection of human rights of detainees at Rudenim Medan.